2000
DOI: 10.1046/j.1471-4159.2000.0750028.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Epilepsy KCNQ2 Gene Results in Neural Hyperexcitability

Abstract: Benign familial neonatal convulsion (BFNC) is a common idiopathic epilepsy with autosomal dominant inheritance. Recently, two novel voltage-dependent potassium channel genes, KCNQ2 and KCNQ3, were identified by positional cloning as being responsible for BFNC. Heterotetramers of the products of these genes form Mchannels and regulate the threshold of electrical excitability of neurons. We disrupted the mouse KCNQ2 gene via gene targeting to study the relationship between KCNQ2 and epilepsy. Homozygous pups (KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 21 publications
13
125
0
2
Order By: Relevance
“…In a phenotype similar to that of a previous Kcnq2 knock-out model (Watanabe et al, 2000), Szt1/Szt1 mice die of lung atelectasis shortly after birth. Szt1/ϩ mice are viable and display decreased seizure threshold and altered sensitivity to drugs that modify the M-channel (Otto et al, 2004), but the specific contribution of the Kcnq2 component of this deletion has not been characterized.…”
Section: Introductionsupporting
confidence: 60%
“…In a phenotype similar to that of a previous Kcnq2 knock-out model (Watanabe et al, 2000), Szt1/Szt1 mice die of lung atelectasis shortly after birth. Szt1/ϩ mice are viable and display decreased seizure threshold and altered sensitivity to drugs that modify the M-channel (Otto et al, 2004), but the specific contribution of the Kcnq2 component of this deletion has not been characterized.…”
Section: Introductionsupporting
confidence: 60%
“…118,119 In addition, mice in which a single copy of the gene for KCNQ2 was disrupted by gene targeting (Kcnq2 ϩ/Ϫ ) showed increased sensitivity to PTZ seizures. 120 The combination of KCNQ2 and KCNQ3 underlies the bulk of the Mcurrent in neurons, 121 although KCNQ5 alone or in combination with KCNQ3 can also contribute to M-current. It is believed that M-current regulates neuronal excitability by determining the neuronal firing threshold, influencing the firing rate, and modulating neuronal responsiveness to synaptic inputs.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…We first focused on KCNQ3 knockout mice (KCNQ3 Ϫ/Ϫ ). These mice were viable, unlike KCNQ2 knockouts (8), and their breeding resulted in progeny that followed Mendelian inheritance (35 KCNQ3 ϩ/ϩ , 72 KCNQ3 ϩ/Ϫ , 34 KCNQ3 Ϫ/Ϫ , n ϭ 21 litters, 141 mice, 2 P ϭ 0.96). As this was not the focus of our study, we did not characterize the mice for any neurological phenotypes.…”
Section: Role Of Kcnq3 In the Imahp In Hippocampusmentioning
confidence: 99%
“…To test this hypothesis, we obtained mice genetically deficient for KCNQ2. KCNQ2 Ϫ/Ϫ mice do not survive because of pulmonary atelectasis; therefore, we investigated KCNQ2 ϩ/Ϫ mice, which have a decreased threshold for chemically induced seizures (8). We found that the peak amplitude of the ImAHP was significantly decreased in KCNQ2 ϩ/Ϫ dentate granule cells compared to KCNQ2 ϩ/ϩ littermates (KCNQ2 ϩ/ϩ : 199 Ϯ 19 pA, n ϭ 7; KCNQ2 ϩ/Ϫ : 81 Ϯ 16 pA, n ϭ 10; P Ͻ 0.0005) (Fig.…”
Section: Contribution Of Kcnq2 To Imahp In Hippocampusmentioning
confidence: 99%